E0197 Effects of prior different intensities exercise on infarct region function and angiogenesis of left ventricle in myocardial infarction rats. (17th November 2010) - Tang, Xiang-Yu; Hong, Hua-Shan; Chen, Liang-Long; Lin, Xiao-Hong; Lin, Jun-Hua; Lin, Zhang
Abstract : Objective: Lifestyle interventions including exercise training have been shown to be a feasible option for the prevention and treatment of cardiovascular diseases. In this study, we investigated the effects of prior different intensities of exercise on infarct region and function and angiogenesis of the left ventricle (LV) in post-myocardial infarction (MI) rats, and further examined the expression of VEGF proteins in the left ventricle. Methods: Male Sprague–Dawley rats were randomly assigned to six groups. The exercised rats underwent a daily 60-min treadmill exercise, 5 d/wk, for 6 wk. Different treadmill speeds were carried out in the high intensity exercise group (HIE-MI group, 30 m/min), moderate intensity exercise groups (MIE-Sh and MIE-MI groups, 21 m/min), low intensity exercise group (LIE-MI group, 12 m/min), respectively, whereas the untrained rats (Sed-Sh and Sed-MI groups) remained sedentary. At 6 wk, 24 h after the last treadmill exercise or the corresponding sedentary protocol, all rats underwent either acute MI (LIE-MI, MIE-MI, HIE-MI and Sed-MI groups) or sham MI operation (MIE-Sh and Sed-Sh groups). Then, all rats were sacrificed at 7d after recovery. Echocardiographic and haemodynamic measurements were performed at the end of the experimental protocol, and hearts were sampled for histological and molecular analysis. The infarct regions were analysed by using Masson's trichrome staining; intramyocardial microvessels were detected by using Factor VIII-related antigen staining; and cardiac VEGF protein levels were determined by Western blotting analysis. Results: Compared with Sed-Sh group, MIE-Sh group ameliorated left ventricular function and increased microvessels intensity, though the difference was not significant. Compared with Sed-MI group, MIE-MI and HIE-MI groups significantly reduced left ventricular infarct size, improved haemodynamic parameters, increased fractional shortening, scar thickness and microvessel density, but LIE-MI rats only had slight, and non-significant effect on these parameters. In addition, the differences between MIE-MI and HIE-MI rats were significant in haemodynamic parameters and microvessel density. Interestingly, compared with Sed-MI group, the exercised hearts displayed higher levels of VEGF protein in MIE-MI and HIE-MI groups. However, there was no significant difference between MIE-MI and HIE-MI groups. Conclusion: Moderate intensity running exercise before acute MI improved LV function, reduced scar size, increased scar thickness and microvessel density in the post-MI rat. Additional higher intensity exercise could have little further effect. Low intensity exercise may be beneficial, but not sufficient to improve MI. Moderate and high intensity running upregulated the expression of VEGF protein, and contributed to the increased microvessels, which may partly benefit cardiac function after MI.